Avaliação da inibição da prolil oligopeptidase, dipeptidil peptidase e acetilcolinesterase por constituintes de plantas nativas do bioma Pampa- RS. Parâmetros bioquímicos e comportamentais de Phyllanthus tenellus. - Santos, Maura Zubiaurre dos (2016)
In this work six native species of Biome Pampa- RS were selected: Spermacoce poaya, Borreria verticillata, Galianthe fastigiata (Rubiaceae), two species of Hypericum: Hypericum brasiliense e H.connatum e Phyllanthus tenellus in order to assess the species with the highest inhibitory potential against POP. Therefore, we performed the phytochemical study of the CE and fractions of the species Hypericumbrasiliense, Hypericum connatum and Phyllanthus tenellus. The fractionation of the species resulted in the isolation of the following compounds: chlorogenic acid (1), quercetrin (2), rutin (3), quercetin (4) and isoquercetrina (5). From the specie P. tenellus the main constituent of ethyl acetate fraction the ellagitannin corilagin was isolated (6) and the flavonoids rutin (7) and (8) vitexin 2 "-O-rhamnoside. The structures of the isolated metabolites were elucidated by 1H and 13C NMR, mass spectrometry and HPLC. The extracts, fractions and isolated compounds were evaluated as inhibitors of prolyl oligopeptidase (POP), dipeptidyl peptidase (DPP IV) and acetylcholinesterase (AChE). All the tested samples of the genus Hypericum showed inhibitory activity of POP. In contrast, the DPP IV inhibitor effect was not significant for all extracts and tested substances. In relation to Phyllanthus tenellus, all fractions and corilagin demonstrated inhibitory potential against POP, except the aqueous fraction that showed less potential for inhibition. Against AChE and DPP IV it was found that only the dichloromethane fraction presented inhibitory potential. The permeability assay (PAMPA) of the hydroalcoholic extract of H. brasiliense showed that the quercetin features moderate permeability 2,19x10-7cm. The analysis of hydroalcoholic extract of P. tenellus showed that the POP inhibitor corilagin is able to pass through the phospholipid membrane by passive diffusion showing moderate permeability 1,26x10-7cm. The plant extract significantly decreased the time of stererotypy in mice, mainly at the dose of 5mg/Kg of CE, such effect was observed both in the acute treatments and in the subchronic treatment. In addition, the CE reduced reactive oxygen species in the striatum and hippocampus.